Korelasi antara Kadar Karbon Monoksida di Udara dan Kadar COHb pada Pedagang Kaki Lima - Sulistio, Ahmad Rizik; Dhanti, Kurnia Ritma; Sulistiowati, Retno; Juwita, Dina Ratna (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2024)
Background: Air pollution is a foreign material or substance in the air that causes changes in the composition of the air from its normal state. Carbon monoxide (CO) is a colorless and odorless gas that can be dangerous if inhaled in large quantities. Sources of CO gas in the air include motor vehicles, as well as household items such as heaters that use kerosene and gas stoves. Carbon monoxide will replace oxygen in red blood cells, which can increase carboxyhemoglobin levels in the blood. Street vendors are people who sell goods and services in public spaces, especially on sidewalks or road shoulders, so they are at risk of being exposed to CO gas continuously. Method : This study uses an observational approach with a cross-sectional research design. The population in this study were street vendors on roads that are frequently passed by vehicles and rarely passed by vehicles as many as 30 samples, with a purposive sampling method. Results : CO levels in locations frequently passed by vehicles were 13 ppm while in places rarely passed by vehicles were 11 ppm and had an average COHb level of respondents in locations frequently passed by vehicles of 0.64% while in respondents in locations rarely passed by vehicles of 0.49%. Conclusion : There is a significant difference between COHb levels in street vendors on roads frequently and rarely passed by vehicles in the Purbalingga area, as evidenced by the Independent T Test result value of p = 0.010 (<0.05). There is a relationship between carbon monoxide levels and COHb levels in street vendors in the Purbalingga area, as evidenced by a p value of 0.001 (p <0.05). The Spearman correlation value of 0.555 indicates a strong relationship. Keywords : Air Pollution, carboxyhemoglobin (COHb), Carbon Monoxide, Street Vendors